PENCEGAHAN KECELAKAAN KERJA PADA BAGIAN PLANT INDUSTRI SEMEN - Taufan, Mohamad; Sulistyadi, Kohar (Universitas Sahid Surakarta, 2012)
The cement industry in overall activity involves human labor potential for accidents. Efforts to prevent the accidents of work needs to beÂ done in the suggestions formulation proposed work as an early warning system in the prevention of occupational accidents. Identification of the need for workers to consider are: 1) The imbalance between the engine speed and the ability to work so that operators get tired faster, 2) lack of balance between workload and energy intake workers, 3) labor work movement uneconomical cause fatigue and pain in a limb, 4) environmental conditions that are not appropriate factory requirements would have a negative impact on the health and performance of the operators. Methods and principles used need to set up a working system components consisting of: 1) human beings with all the properties and limitations, 2) material, 3) Supplies and Equipment work, 4) working environment so that the achieved level of efficiency and productivity high and prevent accidents employment. The conclusions are based on studies that work accidentsÂ is a psychological fatigue caused by physical environmental factors is not supported, such as heat , a lot of dust, and the high noise, and physiological fatigue occurs due to imbalance between the engine speed with the speed of the operators work, how to work and conditions of work stations is not ergonomic.